The Limpopo–Mpumalanga–Eswatini Escarpment—Extra-Ordinary Endemic Plant Richness and Extinction Risk in a Summer Rainfall Montane Region of Southern Africa - Clark, Vincent Ralph; Burrows, John E.; Turpin, Barbara C.; Balkwill, Kevin; Lötter, Mervyn; Siebert, Stefan J. (Frontiers in Ecology and Evolution, 2022)
Climatic, edaphic, and topographic differences between mountains and surrounding lowlands result in mountains acting as terrestrial islands with high levels of endemic biota. Conservation of mountains is thus key to successful biodiversity conservation. The Limpopo–Mpumalanga–Eswatini Escarpment (LMEE) in South Africa and the Kingdom of Eswatini is one of the largest components of southern Africa’s Great Escarpment. Despite botanical collecting effort over 150 years, there has never been a holistic and comprehensive synthesis of plant endemics data for the LMEE. For the first time, we define the LMEE as an orographic entity, covering 53,594 km2; it forms a contiguous highland area from the Pongola River in the south, north to the Woodbush area, and includes rugged western Eswatini. Using exhaustive literature mining, coupled with combined decades of fieldwork by the authors, and up-to-date taxonomic assessments of the 46 undescribed species, we provide the first robust list of plant endemics for the LMEE. The LMEE has 496 endemic plant taxa, comprising 10.7% of the provisional flora (4,657 taxa). This is more than double the endemic plant taxa in the Drakensberg Mountain Centre (DCM), and may be the richest concentration of montane endemics in southern Africa outside of the Core Greater Cape Floristic Region. Grassland hosts the largest number of endemics (74.2%), followed by Savanna (26.6%), then Forest (7.7%). Most endemics of conservation concern occur in Grassland (68.4%), in which one is Extinct and two are Extinct in the Wild. Evolutionary partitioning between Grassland, Savanna and Forest is suggested by low introgression of Biomes at family and genus level, and by a dominance of life-forms adapted to open habitats. High threat statuses for Grassland endemics can be attributed to the historical transformation of almost 20% of Grassland to forestry pre-1990, and ongoing degradation of primary Grassland. With conservation area coverage only 11.1% of the LMEE, the exceptional richness of the endemic flora—combined with major conservation threats—suggest that the LMEE should become a major focus of conservation effort between South Africa and Eswatini as a matter of urgency.